Digital trade in Europe and Central Asia - Shawn W. Tan (Asian Development Bank Institute (ADBI), 2017)
The Internet greatly increases firms' potential to produce new goods and service for new markets. The Internet is also having a dramatic impact on services, especially in the retail, trade and finance sectors, by enabling firms to digitize their products and deliver them over long distances. This paper considers how the Internet can increase exports by reducing trade costs, discusses how e-commerce is transforming sales to both domestic and foreign consumers, and considers how the Internet is making firms more mobile. Despite the enormous potential benefits, the use of the Internet to conduct digital trade is relatively limited in Europe and Central Asia (ECA). The paper focuses on the broad range of developing and developed countries in the ECA region, whose experience will have relevance for many countries. The policy priorities for governments are then reviewed, followed by the new challenges for policy.
Keywords: F10; F13; O10; L81; O52; O53; 330; e-commerce; international trade; Internet; trade costs; firm location; Europe and Central Asia